PERBEDAAN PEMBELAJARAN MENGGUNAKAN TEORI DIENES TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEMESTER 1 TAHUN AJARAN 2016/2017 - Soegandini, Soegandini; Anugraheni, Indri (Universitas Muria Kudus, 2017)
This study was conducted to determine the difference of learning outcomes with the application of Mathematics learning with the application of Dienes Theory learning and the application of conventional learning in the fourth grade students of 02 N Bener Tengaran District in the first semester of academic year 2016/2017. This study is a quasi-experimental study. The design of this study used Posttest Only Control Design, that there were two groups selected at random, and then treated, then after the posttest treatment was given to determine the final result if there is a significant influence of learning by using Dienes Theory. The subjects of this study were the students of grade IV N Bener 01 with the number 32 and SD 02 N Bener Kabupaten Tengaran amounted to 34 students. The group was divided into two groups namely the class II SD N Bener experiment with the application of learning theory of Dienes, while the control group 01 SD N Bener was given the application of conventional learning. The average result of posttest score that has been done on control and experiment group is 76.06 and 79.26. While the test results are known 7,700 t-test with a significance value of 0.002. Based on t-test results and significance values of 0.002 ˂ 0.05, there is a significant difference in learning using Diene Theory of conventional learning. Based on posttest result in control group and experiment group, data analysis by using t-test, it can be concluded that there are differences of learning result of Mateatika using Dienes Theory and conventional learning on students of SD N Bener 02 District of Tengaran semester 1 academic year 2016/2017.